Frequency of Acute Peritonitis Secondary to Various Sites of Viscus Perforation in a Tertiary Care Hospital - Muhammad Daud; Atta Ullah Arif; Qurat Ul Ain; Ihtisham Ul Haq; Faryal, Marya; Waseem Ullah (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency and sites of acute peritonitis in patients with viscus perforation presenting to Lady Reading Hospital, Peshawar. Study Design: Cross-sectional study. Place and Duration of Study: Department of General Surgery, Lady Reading Hospital, Peshawar, Pakistan, from Jan to Aug 2025. Methodology: This study involved 143 patients of both genders aged between 18 and 60 years presenting with viscus perforation. All patients underwent CT imaging for confirmation of viscus perforation and assessment for acute peritonitis based on fever (≥101°F), positive ascitic fluid bacterial culture, and absolute polymorphonuclear leukocyte (PMN) count ≥250 cells/mm³ in ascitic fluid. Age, gender, socioeconomic status, educational level, and perforation sites were analyzed, and a chi-square test was used with significance set at p≤0.05. Results: The mean age of patients was 38.3±11.9 years. There were 89(62.2%) male and 54(37.8%) female patients. Out of 143 patients with viscus perforation, 35(24.5%) developed acute peritonitis. The sites of perforation leading to acute peritonitis were: colon 15 (42.9%), small intestine 16 (45.7%), appendix 2 (5.7%), and stomach 2 (5.7%). Longer duration of symptoms (p-value=0.003) and lower socioeconomic status (p-value=0.021) had significant associations with development of acute peritonitis. Conclusion: Acute peritonitis secondary to viscus perforation was found in approximately one-quarter of patients presenting to our center. Small intestine and colon perforations were the most common sites leading to acute peritonitis. Delayed presentation and poor socioeconomic conditions were significant risk factors for developing acute peritonitis following viscus perforation.